Multivariate statistical analysis treatment of DSC thermal properties for animal fat adulteration - Dahimi, Omar; Abdul Rahim, Alina; Mohammed, Abdulkarim Sabo; Hassan, Mohd Sukri; Zam Hashari, Shazamawati; Abdul, Siti Mashitoh; Saadi, Sami (Elsevier, 2014)
The adulteration of edible fats is a kind of fraud that impairs the physical and chemical features of the original lipid materials. It has been detected in various food, pharmaceutical and cosmeceutical products. Differential scanning calorimetry (DSC) is the robust thermo-analytical machine that permits to fingerprint the primary crystallisation of triacylglycerols (TAGs) molecules and their transition behaviours. The aims of this study was to assess the cross-contamination caused by lard concentration of 0.5–5% in the mixture systems containing beef tallow (BT) and chicken fat (CF) separately. TAGs species of pure and adulterated lipids in relation to their crystallisation and melting parameters were studied using principal components analysis (PCA). The results showed that by using the heating profiles the discrimination of LD from BT and CF was very clear even at low dose of less than 1%. Same observation was depicted from the crystallisation profiles of BT adulterated by LD doses ranging from 0.1% to 1% and from 2% to 5%, respectively. Furthermore, CF adulterated with LD did not exhibit clear changes on its crystallisation profiles. Consequently, DSC coupled with PCA is one of the techniques that might use to monitor and differentiate the minimum adulteration levels caused by LD in different animal fats.